Bringing Pictorial Space to Life: computer techniques for the analysis of paintings - Criminisi, Antonio; Kemp, Martin; Zisserman, A. (2002)
This paper explores the use of computer graphics and computer vision techniques in the history of art. The focus is on analysing the geometry of perspective paintings to learn about the perspectival skills of artists and explore the evolution of linear perspective in history. Algorithms for a systematic analysis of the twoand three-dimensional geometry of paintings are drawn from the work on “single-view reconstruction” and applied to interpreting works of art from the Italian Renaissance and later periods. Since a perspectival painting is not a photograph of an actual subject but an artificial construction subject to imaginative manipulation and inadvertent inaccuracies, the internal consistency of its geometry must be assessed before carrying out any geometric analysis. Some simple techniques to analyse the consistency and perspectival accuracy of the geometry of a painting are discussed. Moreover, this work presents new algorithms for generating new views of a painted scene or portions of it, analysing shapes and proportions of objects, filling in occluded areas, performing a complete threedimensional reconstruction of a painting and a rigorous analysis of possible reconstruction ambiguities. The validity of the techniques described here is demonstrated on a number of historical paintings and frescoes. Whenever possible, the computer-generated results are compared to those obtained by art historians through careful manual analysis. This research represents a further attempt to build a constructive dialogue between two very different disciplines: computer science and history of art. Despite their fundamental differences, science and art can learn and be enriched by each other’s procedures. A longer and more detailed version of this paper may be found in [5].